Ways of forming the readiness of future teachers to manage students' independent work (Pedagogy of Higher and Secondary Education, 2012)
Lavrentyeva A. A. Ways of forming the readiness of future teachers to manage students' independent work.In article approaches reveal, ways of formation of readiness of the future teachers to management of independent work of pupils in the course of vocational training are allocated, the content and structure of this difficult personal formation moves.
Keywords: professional readiness; independent work